Complete phylogeny and historical biogeography of true rosefinches (Aves: Carpodacus). (29th August 2013) - Tietze, Dieter Thomas; Päckert, Martin; Martens, Jochen; Lehmann, Henriette; Sun, Yue‐Hua
Abstract : True rosefinches (Aves: Carpodacus ) are restricted to Eurasia, and 19 out of 25 species occur in the Sino‐Himalayas, making this the likely centre of origin. To test this hypothesis, suggested species splits had to be evaluated and potential further cryptic diversity unravelled. A taxon‐complete dated molecular phylogeny was reconstructed using maximum‐likelihood and Bayesian methods. Maximum‐parsimony and likelihood approaches were applied to deduce ancestral areas. Rosefinches, including the widespread Carpodacus erythrinus (Pallas, 1770), originated in south‐west China (and the Himalayas) 14 Mya, and gave rise to a smaller clade consisting of C. erythrinus, Haematospiza sipahi (Hodgson, 1836), and Chaunoproctus ferreorostris (Vigors, 1829), and a larger clade with 22 species. The latter split into four major lineages through vicariance during the uplift of the Himalayas. The suggested species splits of dubius from Carpodacus thura Bonaparte & Schlegel, 1850, formosanus from Carpodacus vinaceus Verreaux, 1871, grandis from Carpodacus rhodochlamys Brandt, 1843, verreauxii from Carpodacus rodopeplus (Vigors, 1831) (even polyphyletic) could be supported, whereas the suggested split of severtzovi from Carpodacus rubicilla (Güldenstädt, 1775) appears to be too young, and should be considered intraspecific. On the other hand, the central Asian lineage of Carpodacus synoicus Temminck, 1825 deserves species rank [ Carpodacus stolickae (Hume, 1874)]. The Carpodacus eos / pulcherrimus complex consists of four lineages, pulcherrimus / argyrophrys and davidianus [ Carpodacus pulcherrimus s.s. (Moore, 1856)], and eos and waltoni [ Carpodacus waltoni (Sharpe, 1905)]. © 2013 The Linnean Society of London